Purification of human gamma interferon receptors by sequential affinity chromatography on immobilized monoclonal antireceptor antibodies and human gamma interferon (The Rockefeller University Press, 1987)
mAbs against human IFN-gamma (huIFN-gamma) receptors were obtained by immunizing a BALB/c mouse with eluates from immobilized recombinant huIFN-gamma (rhuIFN-gamma) on which lysates of enriched Raji cell membranes had been adsorbed. mAbs were selected for competitive inhibition of receptor binding of 125I-labeled rhuIFN-gamma. The following additional properties suggest that these antibodies are specific for huIFN-gamma receptors: they bind to the surface of human cells expressing IFN-gamma receptors but not to heterologous cells; this binding is inhibited competitively by addition of rhuIFN-gamma; the number of binding sites revealed by direct binding of 125I-labeled rhuIFN-gamma correlates with the amount of antigen recognized by the mAbs on different cell lines. A Triton X-100 extract of a membrane- enriched fraction of human Raji cells was affinity purified with these mAbs and the eluates from such columns were further purified on immobilized rhuIFN-gamma. As revealed by SDS-PAGE, the final eluate contained two major protein bands with approximate Mr of 90,000 (p90) and 50,000 (p50), respectively. Both proteins were able to specifically bind 125I-labeled rhuIFN-gamma upon electroblotting to nitrocellulose. This binding could be inhibited by the huIFN-gamma receptor mAbs, suggesting that the same epitopes are recognized on p90, p50, and on the cell surface. Therefore, these proteins most likely represent at least a part of huIFN-gamma receptors.